THE STORY OF THE LAST ENCOUNTER OF BRITAIN WITH FRANCE - DEHELEAN, Cătălin (Studia Universitatis Babeș-Bolyai Philologia, 2020)
The story of the last Encounter of Britain with France. This study is about a story which narrates an important event for British culture. Literary theory postulates that reading any story has several layers of interpretation. Reading this story is by no means an exception. Depending on the approach one can identify various elements which relate to legends, myths and folktales. This article presents a story of an episode which has an almost legendary place in British culture. The narrative speaks of a French interaction with the British. This took place in a place in Wales called Fishguard in 1797. Its legendary feature is given by the unexpected turn of events. In other words, an otherwise serious event is quasi-comical in nature. This story also contains a mythical element. It is said to have been an action of the local women. The local women are said to have dressed in their traditional attire. This display is said to have scared the French into submission. The entire story is being told by the locals as part of their inherited tradition. They have identified with the story to such an extent that they have even created a material culture around it and have put it on display. REZUMAT. Povestea ultimei întâlniri a Marii Britanii cu Franța. Acest studiu prezintă narațiune unui eveniment important pentru cultura britanică. Teoria literară postulează că lectura oricărei narațiuni are mai multe nivele de interpretare. Lectura acesteia nu este nicidecum o excepție. În funcție de abordare, se pot identifica diferite elemente care se referă la legende, mituri și povești populare. Acest articol prezintă povestea unui episod care are un loc aproape legendar în cultura britanică. Narațiunea aceasta vorbește despre o interacțiune dintre francezi și britanici. Acest lucru a avut loc într-un loc din Țara Galilor numit Fishguard în 1797. Trăsătura sa legendară este dată de o turnură neașteptată a evenimentelor. Cu alte cuvinte, un eveniment altminteri serios are o natură cvasi-comică. Această poveste conține și un element mitic. Este vorba despre o acțiune a femeilor din partea locului. Se spune că acestea s-au îmbrăcat în ținuta lor tradițională. Se spune că această apariție i-ar fi speriat pe francezi să se supună. Întreaga poveste este spusă de localnici ca parte a tradiției lor moștenite. Ei s-au identificat cu povestea într-o asemenea măsură încât au creat chiar o cultură materială în jurul ei și au expus-o. Cuvinte cheie: narațiune, mit, legendă, Franța, Marea Britanie.